Collection, extraction, fractionation and isolation of phytochemical from pandanaceae species / Afra Nahdia Marizan Nor - Marizan Nor, Afra Nahdia (2006)
The main objective of this project is to isolate as many possible phytochemical constituents of a Pandanaceae species. The study has been performed by collecting, extracting, fractioning, isolating and identifying the chemical constituents of a Pandanaceae species. Firstly, a species of Pandanaceae collected from a secondary jungle in Sungai Lembing, Pahang have been utilized to perform the extraction process by using two solvents, petroleum ether and methanol. The two extracts were subjected to fractionation process by column chromatography technique. Isolation process takes place after the detection of possible compound of interest on the TLC plate. Preparative TLC had been used to isolate the compound(s). The compound(s) will be sent for identification by using Nuclear Magnetic Resonance (1H NMR) spectrometer, Infrared (IR) spectrometer and Ultra Violet (UV) spectrometer. Even though the compounds of desire have failed to be isolated, we managed to identify the presence of several compound(s) by using the TLC technique.